Use of soybean flour medium for the production of rennin-like enzyme and inhibition of aflatoxins by Aspergilli - and A.A. BASHEER, H.A. HADWAN, S.R. ALANI, L.R. HASSAN (Indian Phytopathology, 2002)
Production of a rennin-like enzyme by 3 isolates of A. flavus and 1 isolate of A. parasiticus on different media was studied. Production of the enzyme was max. on soyabean flour media. High enzyme production in this medium also inhibited the production of aflatoxins by these fungi.